1998
DOI: 10.1152/jappl.1998.84.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Stop-flow studies of distribution of filtration in rat lungs

Abstract: The stop-flow approach was used to investigate where filtration occurs in the pulmonary vasculature after elevation of left atrial pressure and aspiration of HCl. Rat lungs were perfused for 11 min at zero left atrial pressures, and then flow was stopped for 10 min and left atrial pressures were increased to 20 cmH2O. Thereafter, 3HOH was instilled into the air spaces, and the pulmonary vasculature was flushed by perfusing it from the pulmonary artery to left atrium (anterograde flush) or in the opposite direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Lung lymph flow studies not only measure transpulmonary fluid dynamics but also include lymph flow from non-pulmonary tissues (Demling & Gunther, 1982;Drake et al 1986) and the conducting airways (Wagner et al 1998). Gravimetric lung-fluid dynamic studies only detect variations in total lung water and are unable to account for alterations when changes are to be contributed to the vascular, interstitial and/or cellular compartments in lungs (Lin et al 1998). Methods in the present study provide accurate results acutely in an exercising subject, which can be applied to other animals and humans, in contrast to gravimetric lung studies, which require stagnant experimental conditions, or lymphatic studies, which require extensive surgery and chronic instrumentation.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Lung lymph flow studies not only measure transpulmonary fluid dynamics but also include lymph flow from non-pulmonary tissues (Demling & Gunther, 1982;Drake et al 1986) and the conducting airways (Wagner et al 1998). Gravimetric lung-fluid dynamic studies only detect variations in total lung water and are unable to account for alterations when changes are to be contributed to the vascular, interstitial and/or cellular compartments in lungs (Lin et al 1998). Methods in the present study provide accurate results acutely in an exercising subject, which can be applied to other animals and humans, in contrast to gravimetric lung studies, which require stagnant experimental conditions, or lymphatic studies, which require extensive surgery and chronic instrumentation.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Panel C: Some of the concentrated perfusate is lost through defects in the pulmonary exchange vessels. 3 HOH from the airspaces occurred (9). In the earlier experiments, we instilled the 3 HOH at the end of the equal-pressure-flow period and found that increases in concentrations of FITC-dextran appeared in venous outflow samples before 3 HOH was detected.…”
Section: Discussionmentioning
confidence: 85%
“…The actual causes for small losses of Evans blue from the vasculature in some of these studies remain uncertain. In our previous study, we found that increases in FITC-dextran relative to baseline venous concentrations (rather than arterial concentrations) were similar to increases in concentrations of albumin in the perfusate, suggesting that increases in FITC-dextran concentrations above venous baseline levels can be reliably used to estimate transudation (9). Furthermore, the similarity between the calculated volume of fluid lost by ultrafiltration and the volume of perfusate that entered the vasculature from the arterial and venous reservoirs during the equal-pressure interval suggest that this method of determining transudation is appropriate.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations